Fine tuning the athlete for competition - Browning, M.
Athletic preparation for competition involves the development of each individual's physical and mental attributes in accordance with the requirements of their chosen sport. Fine tuning the athlete for competition does not commence 3-4 weeks out from a major competition but rather from the first training session, and is the sum of all training sessions performed in the lead up to competition. Great Performance requires a defined outcome to ensure that neither athlete, coach nor support staff lose direction. Well thought out goals with a corresponding action plan ensures each session has a defined outcome. It is imperative that all members of the athlete's support network, as well as the athlete, understand and agree with the action plan ensuring a successful preparation.